(3eSGFd aj GdJUhas
(3ChdgG (B:s
(3ai GdcGai ai HGH MOhK GdESJeGQ bGd Ef Gddg JHGQc hJYGdi Ndb ESekG HGdMQha s
(3BNQgG (B:s
(3de CPcQg ai Lgg WQjb GdMOK ai cJH Phjg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs